Effect of prosthodontic planning on lateral occlusion scheme: a comparison between conventional and digital planning (Journal of Applied Oral Science, 2015)
Recently, digital wax-up is proposed as a tool to aid prosthodontic planning. However, there are no data about the effect of prosthodontic planning on lateral occlusion scheme. Objective : This study aims to evaluate the impact of conventional and digital prosthodontic planning on lateral occlusion scheme. Material and Methods : Dental models of 10 patients were collected. All models had Angle Class I occlusion and were undergoing prosthodontic treatment that would influence the lateral occlusion scheme. Each set of models had received both conventional wax-up and digital wax-up. In relation to the lateral occlusion scheme, the following variables were evaluated: the prevalence of the different lateral occlusion scheme, number of contacting teeth and percentage of each contacting tooth. Four excursive positions on the working side were included: 0.5, 1.0, 2.0 and 3.0 mm from the maximal intercuspation position. Results : The lateral occlusion scheme of the two wax-up models was subjected to alterations following excursion. There was a tendency for the prevalence of canine-guided occlusion to increase and for the prevalence of group function occlusion to decrease with increasing excursion. The number of contacting teeth was decreasing with the increasing magnitude of excursion. For the 0.5 mm and 1.0 mm positions, the two wax-ups had significantly greater contacts than the pre-treatment models, while at the 2.0 mm and 3.0 mm positions, all the models were similar. For all models, canines were the most commonly contacting teeth, followed by the teeth adjacent to them. No difference was observed between the two wax-ups in relation to the number of contacting teeth. Conclusion : Although the prosthodontic planning had influenced the pattern of the lateral occlusion scheme and contacts, there was no difference between the conventional and digital prosthodontic planning.